The Strategic Management and the Illegality: a case study on the fighting against piracy in Brazil - Machado, Solange Mata; Mello, Rodrigo Bandeira de (Review of Business Management, 2013)
Multinational companies that suffer from the impact of piracy must recognize the important social and political differences between the local market and the international market to formulate their integrated market and nonmarket strategies. Little is known about the extent to which piracy affects the processes of strategic management of multinational companies operating in emerging countries, where institutional failures restrict the market, or about the type of nonmarket activities used by these companies to achieve their goals of political action. To study this phenomenon, three multinational pharmaceutical companies suffering from illegality were investigated. The evidences of the survey showed that there is a global strategic integration – market and nonmarket (BARON, 1995a). The companies that suffer from piracy tend to use a geocentric structure (PELMUTTER, 1969) formulating nonmarket centralized strategies with the support of specialists to maximize resources. Locally, the subsidiaries implement the global nonmarket strategies, choosing to perform collective activities - independently of the amount of resources available (HILMANN; HITT, 1999).